A twist in time [large type] : a novel - McElwain, Julie (McElwain, Julie. Kendra Donovan series., 2017)
Lady Dover had plenty of secrets, and her past wasn't quite what she'd made it out to be. Nor is it entirely in the past--which becomes frighteningly clear when a crime lord emerges from London's seamy underbelly to threaten Alec. Joining forces with Bow Street Runner Sam Kelly, Kendra must navigate the treacherous nineteenth century while she picks through the strands of Lady Dover's life As the noose tightens around Alec's neck, Kendra will do anything to save him, including following every twist and turn through London's glittering ballrooms, where deception is the norm--and any attempt to uncover the truth will get someone killed.